An evaluation of the effectiveness of disaster management practices in industries: the case of Zimasco pvt ltd company in Kwekwe - Chanengeta, Rufaro (Midlands State University, 2017)
The study aimed at analyzing the effectiveness of disaster management practices in industries with specific reference to Zimasco Pvt Limited Company. The researcher used qualitative design and used questioners, FGD, interviews and observations as primary methods of collecting data. The study was drawn out of a sample size of 55 respondents and these were able to provide adequate information for the smooth ongoing of the study. This clearly demonstrated how Zimasco Pvt Limited Company has tried its level best to implement disaster management practices such as the prevention and preparedness training offered by the company. However there are times when the disaster management policies are not entirely put into practice .The company has also faced a vast number of challenges in trying to implement disaster management. These include lack of funds, lack of resources, heavy taxation by the government and lack of cooperation of the general workers. However recommendations have been brought forward by the scholar such as removal of tools and machines below standard, implementation of pre training to all workers without discrimination and reporting all hazards that might cause disasters so as to enhance the practicability of disaster management policies which paves way to development.